2010
DOI: 10.1093/sleep/33.4.437
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Caffeine Treatment Prevents Sleep Deprivation-Induced Impairment of Cognitive Function and Synaptic Plasticity

Abstract: The results suggest that long-term use of a low dose of caffeine prevents impairment of short-term memory and E-LTP in acutely sleep-deprived rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
98
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(109 citation statements)
references
References 59 publications
8
98
1
2
Order By: Relevance
“…Hippocampal-dependent learning was assessed using the Mnemonic Similarity Task (Fig. 1B) (Kirwan and Stark, 2007;Yassa et al, 2011;, a validated paradigm sensitive to hippocampal subfield function in humans, particularly pattern separation in the CA3/DG subfield. All task sessions were presented using the Psychtoolbox toolkit within MATLAB (The MathWorks), with task versions (each with unique stimuli) used in a counterbalanced order across the three experimental conditions (rested, deprivation, recovery).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hippocampal-dependent learning was assessed using the Mnemonic Similarity Task (Fig. 1B) (Kirwan and Stark, 2007;Yassa et al, 2011;, a validated paradigm sensitive to hippocampal subfield function in humans, particularly pattern separation in the CA3/DG subfield. All task sessions were presented using the Psychtoolbox toolkit within MATLAB (The MathWorks), with task versions (each with unique stimuli) used in a counterbalanced order across the three experimental conditions (rested, deprivation, recovery).…”
Section: Methodsmentioning
confidence: 99%
“…The Mnemonic Similarity Task allows for the concurrent assessment of two learning measures: the Lure Discrimination Index (LDI or "separation bias") (Kirwan and Stark, 2007; and Recognition Memory Accuracy, with LDI demonstrating greater dependence upon the hippocampus (Brock Kirwan et al, 2012), and specifically the CA3/DG subfield region in particular (Kirwan and Stark, 2007;Bakker et al, 2008;Tamminga et al, 2010;Lacy et al, 2011). LDI is defined as the difference between the proportion of lure items correctly identified as "similar" and the proportion of newly presented foil images incorrectly identified as "similar."…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Caffeine enhances alertness by antagonism of adenosine A1 receptor and increases cAMP signaling through inhibition of phosphodiesterase (Fredholm et al 1999;Wu et al 2009). Chronic caffeine administration has been shown to prevent sleep loss-induced impairment of cognitive function and synaptic plasticity (Alhaider et al 2010b). Another stimulant, modafinil, prescribed for treatment of excessive daytime sleepiness, prevents sleep-deprivation induced cognitive impairments (Moreira et al 2010).…”
Section: Resultsmentioning
confidence: 99%
“…In the context of sleep perturbations and learning, most studies have reported on the presence of cognitive impairments with sleep deprivation by exploring a large array of learning and memory tests including the radial arm maze (44,45), Morris water maze (6,46), contextual fear conditioning (47), and eight-box task (48). However, there is only a paucity of cognitive studies exploring the effects of SF, and those were restricted to short-term SF, the latter using methodologies that were associated with substantial alterations in sleep architecture (4)(5)(6).…”
Section: Discussionmentioning
confidence: 99%